CLASSIFICATION OF COULD WORDS IN GERMAN AND UZBEK - Bekmuratova Shaxnoza Azamatovna, Imyaminova Shuxratoy Salijanovna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The usage tradition is very long and rich in the German-speaking area: "Since the early history of the German language, the twin formulas form a distinctive group of phraseologisms." However, we often encounter the word pairs in the current language, they are spoken and written and are in all They are always a lively, invigorating, and in some cases graphic, ornamentation of human utterances. The present work provides a quick insight into the problem of phraseology in its theoretical part, briefly dealing with its definition, its main features and the classification of phraseologisms. I pay more attention to the characteristics of the considered word pairs, where I mainly follow the terminology, partial classification and the syntactic and semantic structure. The practical part includes the corpus of the German formulas and their Czech equivalents